The Effect of Political Connection and Women Directors on Company Value with Financial Performance as a Mediating Variable - Dyandra Viorica Ivonilenia; Maulida Nurul Innayah; Naelati Tubastuvi; Hengky Widhiandono (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to examine the effect of political connections and women directors on company value with financial performance as a mediating variable. The sampling technique used in this study was purposive sampling. The analysis technique used in this study was multiple linear regression analysis. The results of this study showed that political connections and women directors have a positive effect on financial performance. However, the result showed that political connections and women directors have no effect on company value. Then, the result also showed that financial performance has a positive effect on company value. The results of the mediation test using the Sobel test showed that financial performance is able to mediate the relationship between political connections and company value, while financial performance does not mediate women directors and company value.